2017
DOI: 10.1681/asn.2016070789
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin-Induced Podocyte Injury Is Protease-Activated Receptor Dependent

Abstract: Nephrotic syndrome is characterized by massive proteinuria and injury of specialized glomerular epithelial cells called podocytes. Studies have shown that, whereas low-concentration thrombin may be cytoprotective, higher thrombin concentrations may contribute to podocyte injury. We and others have demonstrated that plasma thrombin generation is enhanced during nephrosis, suggesting that thrombin may contribute to nephrotic progression. Moreover, nonspecific thrombin inhibition has been shown to decrease protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 68 publications
(120 reference statements)
2
51
0
Order By: Relevance
“…Thus, inhibition of aPC by A2M may block the protective role of aPC. In addition, repression of aPC is known to enhance thrombin generation (41), and Kerlin and colleagues recently have shown that thrombin injures podocytes (42). A2M-mediated inhibition of aPC-mediated podocyte protection may simultaneously enhance thrombin-mediated podocyte injury.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, inhibition of aPC by A2M may block the protective role of aPC. In addition, repression of aPC is known to enhance thrombin generation (41), and Kerlin and colleagues recently have shown that thrombin injures podocytes (42). A2M-mediated inhibition of aPC-mediated podocyte protection may simultaneously enhance thrombin-mediated podocyte injury.…”
Section: Discussionmentioning
confidence: 99%
“…Both control-and vorapaxar-treated BTBR ob/ob mice showed significant podocyte loss compared with nondiabetic BTBR WT mice, suggesting that vorapaxar treatment does not affect podocyte apoptosis or survival in this particular model. This is interesting, as thrombin is known to affect podocyte apoptosis (11).…”
Section: Discussionmentioning
confidence: 99%
“…As podocyte loss is an important hallmark of albuminuria, and PAR-1 has previously been described to facilitate both cytoprotective and disruptive signaling in podocytes (10)(11)(12), we next assessed the number of podocytes by WT1 immunostaining. As expected, podocyte numbers were significantly reduced in BTBR ob/ob mice as compared with BTBR WT mice, but vorapaxar treatment did not affect podocyte loss (Fig.…”
Section: Histologic Lesions In Control-and Vorapaxar-treated Btbr Ob/mentioning
confidence: 99%
“…33 It is suggested that thrombin may contribute to progression of proteinuria in animal models of nephrotic syndrome. 34 The role of coagulation activation in SCD pathophysiology is highlighted by a recent study which showed that genetic reduction in prothrombin levels in sickle mice not only resulted in decreased levels of thrombin-antithrombin complexes and D-dimer, but also produced significant reductions in renal complications, including albuminuria, compared with wild type sickle mice. 35 In light of these previous reports, the negative association between D-dimer and both NCR and UACR was surprising and unexpected.…”
Section: Discussionmentioning
confidence: 99%